Influencia De Un Programa Basado En El Juego, Como Estrategia Metodológica Para Fortalecer La Suma, La Resta Y La Multiplicación, En Los Niños De 3° De Primaria De La Escuela Enrique Olaya Herrera De La Ciudad De Armenia (2014)
The present investigation called influence of a play-based, as a methodological strategy to strengthen the addition, subtraction and multiplication, children in 3rd primary school Enrique Olaya Herrera Armenian city program was grounded a comparison of results through a pre and post test. This investigation arose after having carried out the experience of teaching practice, since at one point the students showed interest in some subjects directly related to mathematics, which were worked through play. This research aimed to determine the influence of a game based as a methodological strategy to strengthen the processes in the area of mathematics specific operations such as addition, subtraction and multiplication program. The methodology used in the research was a on " approach " quantitative and quasi experimental "type", the population was third degree : and the sample was part of the 3rd grade A composed of 24 students , for analysis the results of the pre test and post test in order to compare the results of the experimental and control group was implemented , where a statistical software called SPSS version 20, which analyzes the results of the tests are used , significant data showing determining the influence of the program , reaching the conclusion that the game-based program helped strengthen the teaching and learning of mathematical operations ( addition, subtraction and multiplication)